1975
DOI: 10.1159/000301522
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Human Cervical Mucus

Abstract: The antimicrobial property of human uterine cervical mucus was tested in three groups of women. Healthy women, using no contraception, women using an intrauterine device and women receiving hormonal treatment for contraception. Cervical mucus was taken on the 10th, 14th, 18th and 22nd day of the menstrual cycle. Cervical mucus had a strong inhibitory effect on the growth of Micrococcuslysodeicticus in all three groups. The strength of the inhibitory effect on the other microorganisms were in the following orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Cervical mucus has antimicrobial activity which reaches a maximum inhibitory effect on the 14th day and declines towards the end of the cycle. The combined oral contraceptive cancels the antimicrobial activity for a variety of organisms 31 . Cervical secretion possesses a concentration dependent antichlamydial activity which appears to be independent of antibody titres to C. trachomatis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Cervical mucus has antimicrobial activity which reaches a maximum inhibitory effect on the 14th day and declines towards the end of the cycle. The combined oral contraceptive cancels the antimicrobial activity for a variety of organisms 31 . Cervical secretion possesses a concentration dependent antichlamydial activity which appears to be independent of antibody titres to C. trachomatis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the immune factors responsible for the antimicrobial properties of cervical mucus in nonpregnant women. These include a variety of polypeptides with activity against a broad range of microorganisms (2–6), as well as immunoglobulins, mainly in the form of secretory immunoglobulin A (SIgA) and IgG (7–10). Although the immune factors operating during pregnancy have also been studied (11–16), samples have been characterized in some studies as representing “cervical mucus in pregnancy” and in others as “cervical mucus plug” leading to difficulties in collective interpretation of results.…”
Section: Introductionmentioning
confidence: 99%
“…Hein et al concluded that “The high immunoglobulin levels in combination with the presence of phagocytes suggest a potential for adaptive immune defense in the cervical mucus plug, which, together with innate immune factors, may act as an immunological gatekeeper protecting the fetomaternal unit against infection from the vagina” [15]. Although using double cerclage to preserve the mucus plug is somehow new in reproductive research, but the role of mucus plug preventing ascending infections gets back close to the time when traditional single cerclage was introduced [16, 17]. Using a double cerclage procedure can be supported by two plausible mechanisms; one being double strengthened weak cervix, and the other can be preventing ascending infection by preserving the mucus plug [18].…”
Section: Discussionmentioning
confidence: 99%